The Effect of Organizational Culture through Total Quality Management: A Moderated Model of Transformational Leadership - Herlina Tri Wulandari; Harsono Harsono; Indri Indri; Mazlini Adnan (Yayasan Keluarga Guru Mandiri, 2026)
This study examines how Total Quality Management (TQM) affects organizational culture in vocational education, using transformational leadership as a moderating variable. The study was motivated by challenges faced by SMK Negeri 4 Klaten in fostering a culture of caring, contribution, and collaboration to improve school performance and graduate readiness. A quantitative cross-sectional design was employed, involving 307 respondents: teachers, staff, and students. Data were collected through a structured questionnaire measuring Total Quality Management, organizational culture, and transformational leadership. Direct and moderating effects were investigated using Structural Equation Modeling (SEM) with AMOS, backed by validity and reliability tests using Average Variance Extracted, Composite Reliability, and Confirmatory Factor Analysis. The findings reveal that both transformational leadership and total quality management have a major positive impact on organizational culture. Additionally, transformational leadership serves as a moderator, strengthening the link between corporate culture and Total Quality Management. By combining transformational leadership with Total Quality Management in vocational schools, this study adds to the body of knowledge on quality management in education. Practically speaking, the results offer guidance to legislators and school administrators on enhancing leadership skills and creating an organizational culture focused on quality.